Structural, thermal and optical properties of zinc boro-aluminosilicate glasses for optical power amplification - Mudhher, Kawa (2018)
Recently, glasses doped with different rare earth (RE) ions are considered promising materials for lasers and optical amplifier applications. In order to investigate new candidate glasses for optical wave guide, structural, thermal, and optical properties of zinc boro-aluminosilicate glasses have been prepared in addition to different alkali (Li, Na, and K) and alkaline oxides (Mg, Ca, Sr, and Ba). Ten mol% of alkali and alkaline oxides were incorporated into Zinc boro-aluminosilicate glasses within high optical quality. Glasses were fabricated using melt-quenching method and prepared into two forms: well-polished solid state and powders. Samples were characterized using X-ray Diffraction (XRD), attenuated total reflectance-fourier transform infrared (ATR-FTIR) spectroscopy, Raman spectroscopy, thermo-gravimetric analysis (TGA), differential scanning calorimetry (DSC), and optical absorption spectroscopy. The presence of various functional groups such as triangular and tetrahedral-borate (BO3 and BO4) were confirmed by ATR-FTIR and Raman spectra. TGA analysis presented low weight loss for all synthesized glasses. From the DSC profiles the glass transition temperature (Tg), onset crystallization temperature (Tx), and crystallization temperature (Tc), were identified and different related thermal parameters were evaluated. From the optical absorption spectra, cut-off wavelength was calculated, showing a spectral shifting to longer wavelength with alkali (Li→Na→K), and alkaline (Mg→Ca→Sr→Ba) modifiers. Optical band gap energy was also investigated for allowed transitions in UV-Visible region using two methods: indirect and absorption spectrum fitting (ASF). Consequently, it was difficult to designate the best host among seven samples to dope with Rare Earth ions. Based on that, Er3+ was doped with the lowest cut-off wavelength glasses among alkali and alkaline, which are H1 and H4 with Li2O and MgO, respectively. A total of 10 glasses were prepared using melt−quenching techniques with the compositions of (40-x)B2O3 − 10SiO2 − 10Al2O3 − 30ZnO − 10Li2O − xEr2O3 and (40-x)B2O3 − 10SiO2 − 10Al2O3 − 30ZnO – 10MgO − xEr2O3 (mol %) (x= 0.1, 0.25, 0.5, 1.0, and 2.0). Amorphous-like structure was observed for all the prepared glasses using XRD. In order to study the functional groups of the glass composition after the melt-quenching process, Raman spectroscopy was used. All samples were characterized using optical absorption for UV, visible and NIR region. Judd-Ofelt (JO) intensity parameters (Ωλ, λ=2, 4 and 6) were calculated from the optical absorption spectra of two glasses, LiEr 2.0 and MgEr 2.0, which was doped with 2 mol % of Er3+. Furthermore, using Judd–Ofelt intensity parameters, the radiative A (s-1), branching ratio (β), radiative decay lifetimes τrad (μs) of emissions from excited Er3+ ions in LiEr 2.0 and MgEr 2.0 to all lower levels were obtained in this work. In order to investigate these glasses for visible laser applications (green emission), quantum efficiency (η) of 4I13/2 and 4S3/2 levels of LiEr 2.0 and MgEr 2.0 were calculated, with and without 4D7/2, using the radiative decay lifetimes τrad. (μs) and measured lifetimes τexp. (μs). Visible photoluminescence was measured under 377 nm excitation for both LiEr and MgEr glass series within the region of 390−580 nm. Decay lifetimes for emissions at 407 nm, 530 nm, and 554 nm were measured, showing single exponential behavior for all the LiEr and MgEr glass series. Lastly, following the photoluminescence and radiative decay lifetimes (τrad), full-width at half-maximum (FWHM), emission cross-section (σEP) and bandwidth gain (FWHM × σEP) parameters were calculated. Near-infrared photoluminescence under 980 nm excitation was measured for all the LiEr and MgEr glass series in the region of 1420−1620 nm. NIR emissions showed a broadband centered at ~ 1530 nm due to the transition of Er3+: 4I13/2 → 4I15/2. Decay lifetimes for NIR emission at ~1530 nm were measured, presenting a single exponential nature for all the LiEr and MgEr glass series.